Perbedaan VO2 Max antara Penarik Becak dengan Supir Taksi di Kota Surakarta - Shelly Lavenia Sambodo; Balgis .; Novan Adi Setyawan (Nexus Biomedika, 2014)
Background: VO2 Max (maximal oxygen uptake) is a capability of oxygen with maximal capacity that used to the body to perform maximal exercise. The factor that most influence of VO2 Max is a physical activity. Cardiorespiratory endurance can be enhanced objectively by doing exercises or sports regularly, structurally, and continuously performed. Pedicab driver does his job by pedaling a pedicab every day, whereas the taxi driver does his job by driving a taxi every day. The aims of this study are to determine the differences of VO2 Max scores between pedicab drivers and taxi drivers in Surakarta. Methods: This study was an observational analytic with cross-sectional approach. The selection of the samples from the population has been conducted with purposive sampling. This study was conducted in the base of Kosti Solo in Mojosongo and in Surakarta. Two groups of samples, 30 taxi drivers and 30 pedicab drivers with the inclusion criteria (man, age 40 - 50 years; BMI ranged from 18.5 kg/m2 25.0 kg/m2; diastolic blood pressure < 100 mmHg; willing to be responders and filling and approved informed-consent; pursue work at least 5 years) conducted a study using Multistage Fitness Test (MFT), which the test is to run back and forth 20 yards. This value can be converted into the equivalent VO2 Max score using prediction table of the VO2 Max. The data were analyzed using non paired t-test (? = 0.05). Results: The results showed the mean scores predicted of the VO2 Max in pedicab driver was 25.79, while the taxi driver was 20.87. The data were analyzed by using non paired t-test that showed significantly differences between the two study groups, p = 0.000 (p < 0.05). Conclusion: There are significant differences of VO2 Max between the pedicab drivers and taxi drivers in Surakarta. Keywords: VO2 Max, pedicab drivers, taxi drivers, cardiorespiratory endurance, MFT